ANALISIS KELAYAKAN INVESTASI SEBAGAI RENCANA PENGGANTIAN MESIN DENGAN TEKNIK CAPITAL BUDGETING: Studi Pada Perusahaan Tegel Beton Dan Sanitair Warna Agung Pamekasan - Wahyu Maulana; Devi Lestari Pramita Putri (Jurnal Ilmu Manajemen METHONOMIX, 2019)
This study aims to determine the extent of consideration that will be used by companies to assess the feasibility of investment plans for fixed assets of machines using capital budgeting analysis techniques so as to obtain the right decision in making replacement of production machines. The machine replacement uses the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods. This research uses descriptive quantitative research with a case study approach. The object of research is tegel beton dan sanitair “Warna Agung” company located on Jalan Segara No. 150 Pamekasan district. The results showed that it is known that the capital budgeting method in replacing the fixed assets of the machine is feasible to carry out. The calculation results obtained using the NPV method are positive (NPV > 0) with the acquisition result of Rp. 196.062.919, and for the PB method produces the time needed to return investment for 2 years 1 month, where the time is less than the economic life of the fixed assets ie company for 5 years and for the IRR method produces a value of 36.4% where the results are above the discount factor of 25%.